A method for realizing giant expansion material, giant expansion material and application thereof

By annealing the lithium metaborate of the tetragonal phase into a single chamfered phase, the problem of weak volume changes in inorganic materials during thermal deformation is solved, and the huge expansion effect is achieved under mild phase transition conditions, and it is suitable for applications such as thermal switches.

CN117385463BActive Publication Date: 2025-04-15TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311524621.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-15
Publication Date
2025-04-15
Estimated Expiration
2043-11-15

AI Technical Summary

Technical Problem

The volume changes of existing inorganic materials during thermal deformation are weak, and the phase change conditions are harsh, making it difficult to achieve a gentle huge expansion effect.

Method used

The preparation of the giant expanded material is achieved by annealing the lithium metaborate of the tetragonal phase at a temperature of 600-740°C. This method makes the lattice parameters and cell volume change significantly before and after the phase transition, resulting in macroscopic size expansion.

Benefits of technology

The preparation of huge expansion materials under mild phase transition conditions is achieved, with the macroscopic dimensional expansion rate reaching 30-60%, which is suitable for practical applications such as thermal switches.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117385463B_ABST
    Figure CN117385463B_ABST
Patent Text Reader

Abstract

The giant expansion material and the method for realizing the giant expansion material provided by the present application anneal tetragonal lithium metaborate at a temperature of 600-740°C, and the tetragonal lithium metaborate changes its shape. The lithium metaborate structure provided by the present application has an atomic distribution similar to that of diamond and cubic boron nitride, and the structural voids are occupied by ionic groups. The structure has compactness, which can provide structural internal stress during the heating process to force the atoms to redistribute. The tetragonal lithium metaborate structure causes huge volume expansion before and after the phase change, triggering a structural transformation that is directly reflected in the macroscopic size. The phase change conditions are mild and can be applied in practical applications. A larger macroscopic shape change can better realize the function of the thermal switch.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of thermal expansion technology, and in particular to a method for realizing a giant expansion material, lithium metaborate, a giant expansion material, and applications. Background Art

[0002] Thermal expansion is a common phenomenon in nature. Temperature affects the change in crystal size. One type of material will undergo a sudden change in lattice parameters under the action of temperature, and this change will be transmitted to the macroscopic structure through the periodicity of the lattice, ultimately achieving a dramatic deformation of the macroscopic shape. This type of material that undergoes a huge shape change under temperature stimulation has potential application value in the field of thermal switches.

[0003] Crystalline organic compounds with giant expansion properties often have large macroscopic shape changes in bulk crystals during heating. By driving entropy to redirect organic molecules in a specific framework structure, the induced structural phase transition causes a crystal scale change of about 10%. In contrast, the unit cell volume change caused by thermal phase transitions in most inorganic structures is generally around 5%, while ICSD shows that the unit cell volume of diamond and cubic boron nitride has a 53% expansion before and after the phase transition, indicating the potential of inorganic materials in thermally induced deformation. However, the phase transition conditions of these two are relatively harsh, so it is still difficult to allow inorganic materials to undergo huge lattice parameter mutations while also having mild phase transition conditions. Summary of the invention

[0004] In view of this, it is necessary to provide a method for realizing a giant expansion material with mild phase change conditions, a giant expansion material and its application in order to address the technical defects of the prior art.

[0005] To solve the above problems, this application adopts the following technical solutions:

[0006] One of the purposes of the present application is to provide a method for realizing a giant expansion material, comprising the following steps:

[0007] The tetragonal lithium metaborate is annealed at a temperature of 600-740° C., and the tetragonal lithium metaborate undergoes a shape change.

[0008] In some of the embodiments, the tetragonal lithium metaborate is converted into monoclinic lithium metaborate.

[0009] In some embodiments, the tetragonal lithium metaborate is in the form of powder or block crystals.

[0010] In some of the embodiments, the change rates of the lattice parameters a, b, c and the unit cell volume V of the lithium metaborate before and after the phase transition are 37.7%, 2.6%, 2.6% and 33.6%, respectively.

[0011] In some of the embodiments, the lithium metaborate expands significantly in macroscopic size after the phase change, and the expansion rate obtained by calculating the area enclosed by the envelope is 30-60%.

[0012] One of the purposes of the present application is to provide a giant expansion material, which is prepared by the method for realizing the giant expansion material.

[0013] The second purpose of the present application is to provide an application of the giant expansion material in a thermal switch.

[0014] This application adopts the above technical solution, and its beneficial effects are as follows:

[0015] The giant expansion material and the method for realizing the giant expansion material provided by the present application anneal tetragonal lithium metaborate at a temperature of 600-740°C, and the shape of the tetragonal lithium metaborate changes. The lithium metaborate structure provided by the present application has an atomic distribution similar to that of diamond and cubic boron nitride, and the structural voids are occupied by ionic groups. The structure has a compactness, which can provide structural internal stress during the heating process to force the atoms to redistribute. The tetragonal lithium metaborate structure causes a huge volume expansion before and after the phase change, which triggers a structural transformation and is directly reflected in the macroscopic size. The phase change conditions are mild and can be applied in practical applications. A larger macroscopic shape change can better realize the function of the thermal switch. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0017] Figure 1 The lattice parameters and unit cell volume of lithium metaborate provided in the embodiments of the present application vary with temperature. The blue circle, diamond and square correspond to a, b and c of the crystal respectively, and the red ball represents the unit cell volume of the crystal.

[0018] Figure 2 The examples of the present application provide pictures of the 587°C low temperature phase and the 640°C high temperature phase under a microscope.

[0019] Figure 3 Provided in the examples of the present application is a schematic diagram of differential scanning calorimetry results at 25-1200°C.

[0020] Figure 4 The block crystal morphology provided in the embodiment of the present application at different temperatures, the process from 584°C to 687°C, the surface phase change to the complete phase change, and the schematic diagram of the crystal morphology from block to powder state.

[0021] Figure 5 A schematic diagram of phase change provided in an embodiment of the present application, wherein curves 1-5 respectively represent a low-temperature phase, a high-temperature phase after heat treatment of the low-temperature phase, and a low-temperature phase synthesized again from the high-temperature phase, and two cycles are performed in this way. DETAILED DESCRIPTION

[0022] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0023] In the description of the present application, it should be understood that the terms "upper", "lower", "horizontal", "inside", "outside", etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0024] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0025] In order to make the objectives, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0026] The method for realizing the giant expansion material provided in the embodiment of the present application comprises the following steps: annealing tetragonal lithium metaborate at a temperature of 600-740° C., so that the tetragonal lithium metaborate undergoes a shape change.

[0027] It should be noted that: although the structural design of crystalline organic compounds is more free and it is easier to obtain special structures with unconventional properties, their properties do not depend on the topological structure. Therefore, the mechanism behind the properties is not universal, and it is difficult to explore the structure required for the properties. The change in the macroscopic size of crystalline organic compounds caused by temperature is still low (5-20%). Although diamond and cubic boron nitride have shown huge mutation results in this regard, they are not suitable for practical applications due to the harsh phase transition conditions (vacuum, high temperature or high pressure extreme conditions). The structures of diamond and cubic boron nitride are similar, and the unit cell changes caused by phase transition are also the same, indicating that this property depends on the topological structure in inorganic materials. However, in current research, the volume mutation caused by thermally induced phase transition of inorganic materials is still very weak, and has low directionality for structural design.

[0028] Referring to the structural characteristics of diamond, we speculate that the material needs to have the following two characteristics: 1) The structure must be dense to provide internal structural stress during the heating process to force the atoms to redistribute and cause structural changes; 2) It must have ionic groups to reduce the phase change conditions.

[0029] By searching the ICSD library, it was found that the structure of lithium metaborate has an atomic distribution similar to that of diamond and cubic boron nitride, and the structural gaps are occupied by ionic groups, which meets the above requirements. Tests show that the volume increases by 34% after the thermally induced phase transition, and its millimeter-scale single crystals show similar shape deformation. Lithium metaborate has this structural feature, which makes it have the potential of giant expansion material.

[0030] In this embodiment, the tetragonal lithium metaborate is converted into monoclinic lithium metaborate.

[0031] In this embodiment, the tetragonal lithium metaborate is in the form of powder or block crystals.

[0032] In this embodiment, the change rates of the lattice parameters a, b, c and the unit cell volume V of the lithium metaborate before and after the phase transition are 37.7%, 2.6%, 2.6% and 33.6%, respectively.

[0033] See also Figure 1 , the lattice parameters and unit cell volume of lithium metaborate provided in this embodiment vary with temperature, the blue circle, diamond and square correspond to a, b and c of the crystal respectively, and the red ball represents the unit cell volume of the crystal. Figure 1 It can be seen that the crystal cell parameters and unit cell volume of the lithium metaborate change suddenly before and after the phase transition, and the change rates of a, b, c and V are 37.7%, 2.6%, 2.6% and 33.6% respectively. Compared with the organic compound unit cell volume change, it increases several times and also shows obvious shape changes at the macro scale.

[0034] In this embodiment, the lithium metaborate expands significantly in macroscopic size after the phase change, and the expansion rate is 30-60% by calculating the area enclosed by the envelope.

[0035] See also Figure 2 , provided for this embodiment are pictures of the 587°C low-temperature phase (the upper picture) and the 640°C high-temperature phase under a microscope (the lower picture), with the outline of the crystal outlined by pink lines. The figure clearly shows the macroscopic expansion behavior of the crystal, where the heating rate is 0.6°C / min, the temperature rises from 570°C to 650°C, and the front and rear envelope areas expand by 50%.

[0036] See also Figure 3 , which is the result of differential scanning calorimetry from 25 to 1200 °C. The two peaks before and after represent the schematic diagram of phase change and melting, respectively.

[0037] from Figure 3 It can be seen that DSC shows two peaks in the heating process of 25-1200℃, representing phase change and melting respectively. It should be mentioned that the phase change peak will change with factors such as heating rate and sample state, so the temperature range from the first peak at 600℃ to the second peak at 740℃ is the phase change temperature range of lithium metaborate.

[0038] See also Figure 4 , which shows the morphology of tetragonal lithium metaborate block crystals at different temperatures. From 584℃ to 687℃, it undergoes a process of no phase change, surface phase change, and complete phase change. The morphology of the crystal breaks from block to powder state, and the whole process takes 26 minutes.

[0039] It is understandable that if the heating rate increases, the lithium metaborate block crystals will break into powder. The dramatic change in morphology has application value in thermal switches. When the temperature exceeds the target temperature, the lithium metaborate quickly disintegrates into powder as a safety device, disconnecting the device switch. The tetragonal phase and the tetragonal phase can be transformed into each other through temperature and pressure, so as to achieve recycling and save costs.

[0040] See also Figure 5 , where curves 1 to 5 respectively represent the low-temperature tetragonal phase (1), the high-temperature monoclinic phase after heat treatment of the low-temperature tetragonal phase (2), and the low-temperature monoclinic phase synthesized again from the high-temperature tetragonal phase (3). This is the first cycle. Curves 4-5 undergo the same treatment as 2-3 and undergo a second cycle, indicating that the material can be recycled.

[0041] The lithium metaborate structure provided in the present application has an atomic distribution similar to that of diamond and cubic boron nitride. The structural voids are occupied by ionic groups. The structure is compact and can provide structural internal stress during the heating process to force the atoms to redistribute. The tetragonal lithium metaborate structure causes a huge volume expansion before and after the phase change, triggering a structural transformation that is directly reflected in the macroscopic size. The phase change conditions are mild and can be applied in practical applications. Larger macroscopic shape changes can better realize the function of the thermal switch.

[0042] It can be understood that the technical features of the above-described embodiments can be arbitrarily combined. In order to make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0043] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.

Claims

1. A method for realizing giant expansion material, characterized in that: The method comprises the following steps: annealing tetragonal lithium metaborate at a temperature of 600-740° C., wherein the tetragonal lithium metaborate undergoes a shape change, the heating rate is 0.6° C. / min, and the tetragonal lithium metaborate is a block crystal; The time it takes for the tetragonal lithium metaborate to change its shape is 26 minutes; The lithium metaborate expands significantly in macroscopic size after phase change, and the expansion rate is 30-60% by calculating the area enclosed by the envelope.

2. The method for realizing giant expansion material according to claim 1, characterized in that: The tetragonal lithium metaborate is converted into the monoclinic lithium metaborate.

3. The method for realizing giant expansion material according to claim 1, characterized in that: The change rates of the lattice parameters a, b, c and the unit cell volume V of the lithium metaborate before and after the phase transition are 37.7%, 2.6%, 2.6% and 33.6% respectively.

4. Application of the giant expansion material prepared by the method for realizing the giant expansion material according to claims 1 to 3 in a thermal switch.

Citation Information

Patent Citations

  • Preparation method and application of lithium metaborate crystal

    CN106917139A

  • Lithium Metaborate Crystal, Preparation Method and Use Thereof

    US20190345633A1